NESFATIN-1 PROTECTS FROM ACUTE PANCREATITIS: ROLE OF MELANOCORTIN RECEPTORS - ÖZBEYLİ, DİLEK; YÜKSEL, MERAL; KASIMAY ÇAKIR, ÖZGÜR (POLISH PHYSIOLOGICAL SOC, 2019)
Nesfatin-1, a recently discovered peptide, was shown to have anti-inflammatory effects. Acute pancreatitis (AP) is a life-threatening condition caused by various reasons. Although the etiology of AP is well-known, its pathogenesis is not clear. The aim of this study is to investigate the possible anti-inflammatory role of nesfatin-1 and its probable protective underlying mechanisms in an acute pancreatitis model. Caerulein was applied intraperitoneally to induce acute pancreatitis in Sprague-Dawley female rats. Nesfatin-1 was administered 5 minutes before the application of caerulein to determine its potential anti-inflammatory role on AP. Five minutes before nesfatin-1 injection, in order to investigate the underlying mechanism, oxytocin receptor antagonist (atosiban), melanocortin receptor antagonist (HS024), or ghrelin receptor antagonist (cortistatin) were administered. Five minutes after nesfatin-1 administration, two doses of caerulein were applied one hour apart. The rats were sacrified 12 hours after the first caerulein dose for serum and pancreatic tissue sampling. Microscopic damage scoring, malondialdehyde and glutathione levels, myeloperoxidase activity, luminol and lucigenin chemiluminescence levels in pancreatic tissue and amylase, lipase, trypsinogen-2 levels in serum were evaluated. Oxidative damage was decreased with nesfatin-1 treatment in the acute pancreatitis model (P < 0.05 - 0.001). The administration of HS024 reversed the effect of nesfatin-1, via increasing lipase, amylase, trypsinogen-2, malondialdehyde (MDA), myeloperoxidase (MPO) and lucigenin levels (P < 0.05 - 0.01). Atosiban pre-treatment elevated MPO activity, luminol and lucigenin chemiluminescence levels (P < 0.01 - 0.001) and cortistatin increased lucigenin and luminol chemiluminescence (P < 0.05 - 0.01). Although receptor antagonists reversed the effect of nesfatin-1 on related biochemical parameters, no significant difference was found in histological scoring. Our results indicated that nesfatin-1 had an anti-inflammatory effect on acute pancreatitis via mainly effecting melanocortin receptors.
Keywords: nesfatin-1; pancreatitis; oxytocin; melanocortin; ghrelin; reactive oxygen species; oxytocin; lipid peroxidation; nucleobindin-2; REMOTE ORGAN INJURY; PANCREATICOBILIARY INFLAMMATION; NITRIC-OXIDE; EXPRESSION; DAMAGE; RAT; NUCB2/NESFATIN-1; ACTIVATION; GHRELIN; TISSUES